Comorbidity and nutritional status in adult with advanced chronic kidney disease influence the decision-making choice of renal replacement therapy modality: A retrospective 5-year study - Álvarez-García, Graciela; Nogueira Pérez, Ángel; Prieto Alaguero, María Pilar; Pérez Garrote, Carmen; Díaz Testillano, Aránzazu; Moral Caballero, Miguel Ángel; Ruperto, Mar; González Blázquez, Cristina; Barril, Guillermina (Frontiers in Nutrition, 2023)
Background: Nutritional and inflammation status are significant predictors of morbidity and mortality risk in advanced chronic kidney disease (ACKD). To date, there are a limited number of clinical studies on the influence of nutritional status in ACKD stages 4-5 on the choice of renal replacement therapy (RRT) modality. Aim: The aim of this study was to assess whether comorbidity and nutritional and inflammatory status influenced decision-making on the choice of RRT modalities in patients with ACKD.